The Determinant Factors of Patient Satisfaction among Outpatient and Inpatient Services in A Type B Hospital in Indonesia - Suhita, Byba Melda; Fajriah, Asruria Sani; Acob, Joel Rey Ugsang (Fakultas Ilmu-ilmu Kesehatan, 2023)
Healthcare providers have made various efforts to increase patient and community satisfaction with health services. However, large sample size studies have not been conducted to investigate the determinants of community stratification in Indonesia. This research aimed to analyze determinant factors affecting patient satisfaction in a type B hospital. A cross-sectional with an online survey was used and analyzed with path analysis. A total of 884 participants were recruited with the criteria that all respondents were patients aged 17 years and over who visited the inpatient and outpatient hospital. Overall, the value service satisfaction was very good (scored 87.44 score). Moreover, online service directly increased by age (b = 0.68; 95% CI = 0.08 to 1.27; p = 0.026), gender (b = 0.82; 95% CI = 0.15 up to 1.49; p = 0.016), and education level (b = 1.76; 95% CI = 0.86 to 2.66; p <0.001). Moreover, service costs are directly affected by employment (b = 0.67; 95% CI = 0.92 to 1.26; p = 0.023); and product-specific services were directly affected by age (b = 0.74; 95% CI = 0.20 to 1.29; p = 0.008). These findings suggest that education, gender, and age directly affect online services as an indicator of satisfaction.